Data wobbles in hidradenitis suppurativa clinical trials and potential contributing factors: a retrospective review - Corey L. Snyder, MD; Ruby S. Gibson, MD; Stella X. Chen, MD; Martina L. Porter, MD; Alexa B. Kimball, MD, MPH (Wolters Kluwer, 2024)
Background:. In some hidradenitis suppurativa (HS) clinical trial study arms, there is an unexpected decline in efficacy between the penultimate visit and the prespecified primary endpoint week, which we have termed a "wobble." Objective:. We aimed to establish how often study arms in HS programs wobble. Methods:. In a retrospective review, we identified HS clinical trials listed on ClinicalTrials.gov testing systemic, nonantibiotic medications that utilized Hidradenitis Suppurativa Clinical Response (HiSCR) as an outcome measure. We identified study arms demonstrating greater improvement in a visit prior to the primary endpoint week. Baseline subject characteristics were compared between studies with HiSCR wobble and no HiSCR wobble. Results:. A total of 21 studies (randomized control trial [RCT], n = 14; open-label, n = 7) with 35 study drug arms (RCT, n = 27; open-label, n = 8) and 14 placebo arms were identified. HiSCR wobble occurred significantly more often in RCT compared to open-label study drug arms (11/27 [40.7%] vs 0/8 [0%]). In RCT study arms with HiSCR wobble, baseline draining fistula counts were significantly lower (2.3 vs 3.2), and numerically fewer Hurley stage 3 patients (33.2% vs 42.5%), lower weighted total abscess and nodule counts (12.1 vs 12.6), lower weighted dermatology life quality index scores (12.5 vs 14.5), and a higher proportion of female patients (63.9% vs 58.3%) were observed. Limitations:. Include low number of HS clinical trials and insufficient data reported in many studies to assess for wobble, degree of wobble, and to compare all baseline characteristics. Conclusion:. Nonlinear improvement in study arm response occurs in some HS RCTs. Potential contributing factors include a higher proportion of less severe patients at baseline and more female patients.